Bahasa Inggris - Sri Lestari; Titin Dunggio; Arpin (Journal of Health, Technology and Science (JHTS), 2022)
Potassium is a major intracellular cation that plays an important role in cellular metabolism. This study aims to describe the results of examination of blood potassium levels in the elderly in the work area of ​​the Kabila Health Center.This research method uses a quantitative research approach with the type of research used in this study is a descriptive type of research. The results of this study indicate that the results of examination of blood potassium levels in the elderly from 26 respondents obtained normal results as many as 5 samples 919.23%, high as many as 5 samples 19.23%, and low as many as 16 samples 61.54%. The amount of low blood potassium is more because respondents have low potassium intake.Conclusion Based on the risk factors that most influence the results of examination of blood potassium levels in the elderly, namely the lack of consuming foods containing potassium and not consuming very high amounts of potassium.